Do ensino à leitura intertextual de As Parceiras, de Lya Luft - Oliveira, Cleidiane da Silva Vieira (2013)
This paper presents reflections on reading and intertextuality in teaching literature from a reading proposal mediated by cultural gender studies, in order to contribute to the formation of a critical consciousness of the reader. At first, our goal is to identify the mechanisms of their own cultural aesthetic and literary reading, in the second, we analyze gender issues present in the novel The Partner (1980) by Lya Luft. Theoretically, we rely on the concepts of reading and reader proposed by Umberto Eco and Hans Robert Jauss; reading and literature discussed by Ligia Chiappini, William Cherry and Rildo Cosson, and interdisciplinary commented by Marisa Lajolo and Regina Zilberman. The kind of approach we intend to do, the reader aesthetic is one that refreshes and gives meaning to the text, interpreting the unsaid through cooperative movements, conscious and active. For this, we advocate the teaching of literature guided by cultural bias of gender studies. Accordingly, I shall use the concept of |cultural reading| Charlemagne Gomes, for the analysis of the novel The Partner (1980) by Lya Luft. With this, we advocate the search for a way politicized reading based on questioning of hegemonic values and the inclusion of questions of belonging identity, the differences of race, sex, gender, class or belief in teaching literature. We divide this thesis into three chapters. In the first, we will address issues related to the teaching of literature in contemporary and training of the reader, in the second, we discuss about the interdisciplinary dimension of literature and the importance of training the reader aesthetic and cultural, in the latter, present a cultural reading of the novel The partners of Lya Luft, through which we intend to analyze gender issues as marks of ideological struggle for women s rights. We believe that these issues contribute to the interpretation layer ideological texts, for the recognition of voices and silenced and excluded classes and for the formation of contemporary literary reader.